Tax competition in an expanding European Union - Ronald B. Davies; Johannes Voget (University College Dublin, UCD School of Economics, 2009)
This paper empirically examines whether expansion of the EU has increased international tax competition. To do so, we use a simple model of tax competition to determine how a given country weights the taxes of others when choosing its own tax. This indicates that the market potential of a country (which includes both domestic consumption and exports) is the appropriate weight. This is an improvement on the adhoc and often endogenous weighting schemes used elsewhere. Unlike those studies, we find robust evidence for tax competition. In particular, our estimates suggest that EU membership affects responses with EU members responding more to the tax rates of other members. This lends credence to the above-noted concerns.
hdl:10197/2600
Keywords: F1; H2; H7; 330